2021
DOI: 10.1007/s11356-021-16050-3
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in biochemical constituents and nutrients partitioning of Asparagus racemosus in response to elevated atmospheric CO2 concentration

Abstract: Human-induced CO2 emissions since the preindustrial era have accumulated CO2 in the atmosphere which has influenced the plant structure and function including bio-chemical constituents of the plant system. The Himalayan vegetation has been predicted to be more vulnerable and sensitive to climate change. However, it is still not well documented that how atmospheric CO2 concentration will change the biochemical constituents considering nutrients status of Himalayan endangered plants in future climate change. Hen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Elevated CO 2 at 600 and 1000 µmol mol −1 Total phenolics/cyanidin/antioxidant capacity of plantlets increased by high eCO 2 [175] Asparagus racemosus Willd. Elevated CO 2 400, 600, and 800 µmol mol −1 Elevated CO 2 increased the content of total sugars and proteins in leaves and roots [152] Summer savory (Satureja hortensis L.) Elevated CO 2 (620 µmol mol −1 ) Nutrients (K, Ca, P, Mg) and polyphenols were enhanced by eCO 2 under drought stress [176] Caraway (Carum carvi L.) Elevated CO 2 at 400 and 620 µmol mol −1 Higher CO 2 enhanced content of phenolic compounds and flavonoids [177] Barley (Hordeum vulgare L.) and maize (Zea mays L.) eCO 2 level (620 µmol mol −1 ) Barley accumulated anthocyanins, but total phenolics and flavonoids accumulated in maize under As 2 O 3 -NP stress and elevated CO 2 [178] Two species of lemon-grass Elevated CO 2 (620 µmol mol −1 ) eCO 2 increased level of primary and secondary metabolites such as amino acids and phenolics [179] Paris polyphylla var. yunnanensis Elevated CO 2 (800 µmol mol −1 ) A high-CO 2 environment increased the diosgenin content and thus total saponin [180] Glehnia littoralis Fr.…”
Section: Plant Nutrition Under Climate Changementioning
confidence: 96%
See 1 more Smart Citation
“…Elevated CO 2 at 600 and 1000 µmol mol −1 Total phenolics/cyanidin/antioxidant capacity of plantlets increased by high eCO 2 [175] Asparagus racemosus Willd. Elevated CO 2 400, 600, and 800 µmol mol −1 Elevated CO 2 increased the content of total sugars and proteins in leaves and roots [152] Summer savory (Satureja hortensis L.) Elevated CO 2 (620 µmol mol −1 ) Nutrients (K, Ca, P, Mg) and polyphenols were enhanced by eCO 2 under drought stress [176] Caraway (Carum carvi L.) Elevated CO 2 at 400 and 620 µmol mol −1 Higher CO 2 enhanced content of phenolic compounds and flavonoids [177] Barley (Hordeum vulgare L.) and maize (Zea mays L.) eCO 2 level (620 µmol mol −1 ) Barley accumulated anthocyanins, but total phenolics and flavonoids accumulated in maize under As 2 O 3 -NP stress and elevated CO 2 [178] Two species of lemon-grass Elevated CO 2 (620 µmol mol −1 ) eCO 2 increased level of primary and secondary metabolites such as amino acids and phenolics [179] Paris polyphylla var. yunnanensis Elevated CO 2 (800 µmol mol −1 ) A high-CO 2 environment increased the diosgenin content and thus total saponin [180] Glehnia littoralis Fr.…”
Section: Plant Nutrition Under Climate Changementioning
confidence: 96%
“…Furthermore, they discovered that, contrary to expectations, species responded best to a mix of low water and high nutrients, regardless of their origin. Under elevated CO 2 concentrations from 400 to 800 ppm, the accumulation of nutrients, especially K and Mg, was significantly increased, whereas phosphorus was decreased in leaves, stems, and roots of Asparagus racemosus [152]. Ayi et al [157] showed that alternanthera philoxeroides, or alligator-weed, is a common and often invasive plant that is invasive near waterways and tolerant of flooding.…”
Section: Plant Nutrition Under Climate Changementioning
confidence: 99%
“…The increase in leaf dark respiration can result from the direct instantaneous effect of increased CO 2 concentration and the longer-term indirect effect due to changes in leaf composition 23 . The increased carbon assimilation resulting from elevated CO 2 concentrations has enhanced different crop species' growth, productivity, and biochemical constituents 24 . In leguminous plants, eCO 2 concentrations have increased chlorophyll, total starch, sucrose, and total carbohydrate content 25 .…”
Section: Introductionmentioning
confidence: 99%